Intraspecific variation of the caudal fin skeleton in Osteoglossum bicirrhosum Cuvier 1829 (Teleostei: Osteoglossomorpha: Osteoglossidae) - Leal, Maria Eduarda Castro; Brito, Paulo M. (Zootaxa, 2007)
The caudal fin skeleton has been regarded as a major source of characters used in the evaluation of teleostean interrelationships. Despite the increasing number of papers drawing attention to the variability observed within species when large samples are considered, intraspecific variation of this complex remains poorly known for many teleostean groups, and comparative anatomical studies still often rely on a small number of specimens. Within the Osteoglossomorpha, there are few studies concerning instraspecific variation patterns, and many aspects of both the anatomy and homology of the caudal fin skeleton elements are controversial (e.g. epurals versus uroneurals; number of hypurals compounding the “hypural fan”). Given this perspective, we examined the caudal skeleton of 84 specimens of the neotropical osteoglossid fish Osteoglossum bicirrhosum, and described and quantified its morphological variation. We determined that the number of neural spines on the preural centra and hypural fusion patterns showed the greatest variation. Despite the widespread distribution of this taxon, the observed variation appears to be geographically independent, and occurs randomly within populations.